The phenomenon of cyclical fluctuations on the pork market - global perspective = Fenomen wahań cyklicznych na rynku żywca wieprzowego - perspektywa globalna - Stępień, Sebastian; Polcyn, Jan (Zielona Góra: Faculty of Economics and Management Press)
The aim of publication was to recognize the characteristics and morphology of today`s hog cycle. The hypothesis was that known in the economy since the second half of the nineteenth century hog cycle is also a typical phenomenon in the contemporary economy. It is also claimed that cyclical supply changes of pig meat are not synchronized between countries. Fluctuations in production are country-specific and are influenced by local conditions.
Keywords: gospodarka współczesna; fluktuacja produkcji; analiza empiryczna; rynek żywca wieprzowego; wahania cykliczne; ceny; podaż; skala globalna; contemporary economy; fluctuation in production; empirical analysis; pork meat market; cyclical fluctuations; supply; prices; global perspective